Penerapan Model PAKEM Pada Kursus Bimbingan Belajar Gratis di SD Karya Bhakti Medan - Herman Alfredo Turnip; Christina Ria Natal Sitorus Pane; Grace Immanuella C. Hutabarat; Putri Elsarika Purba; Surya Darma Sihombing; Ayu Putri Ani Sagala; Srianti Br. Tobing; Nova Sitinjak; Robin Christ F Sitanggang; Rolan Manurung (Utan Kayu Publishing, 2022)
One of the obstacles to student learning is monotonous learning which makes students inactive and feeling bored so that it affects the achievement of students' cognitive, affective and psychomotor abilities. The purpose of this Community Service activity is to provide free tutoring assistance to students of SD Karya Bhakti Medan Helvetia and also as a means for students to channel their knowledge and concern for children who are undergoing a period of online learning and limited face-to-face learning. This Community Service activity is carried out using the methods of preparation, implementation, and evaluation. Tutoring is carried out using the PAKEM learning model (Active, Creative, Effective, and Fun Learning), so that elementary school students feel more comfortable and less tense in participating in tutoring activities. The results and outcomes achieved are that the tutoring activities carried out can help parents who cannot accompany their children in participating in online learning and also to increase the learning motivation of students at Karya Bhakti Elementary School Medan Helvetia. In addition, parents/guardians of students are grateful for the improvement in their children's academic achievement at school after participating in this tutoring activity. This is because after attending tutoring, students become more enthusiastic in doing school assignments (PR) well and there are no neglected assignments because there is someone who guides them so that students' understanding of the subject matter at school increases with the repetition of the material provided. by tutors (teachers).